“Análisis del aporte cultural de la orquesta sinfónica de Riobamba en el imaginario social de los habitantes del cantón Riobamba en el periodo noviembre 2015- noviembre 2016”. - Montoya Méndez, Paola Gabriela (2017)
The main objective of this research is to analyze the cultural contribution of the Riobamba symphony orchestra in the social imaginary of the inhabitants of the canton Riobamba in the period November 2015- November 2016. The same one that was carried out on the little knowledge about the cultural contribution offered by the symphony orchestra to the city. Theoretically , the work was based on the independent variable such as the symphony orchestra and the dependent variable that was the social imaginary; the method applied was inductive since an analysis was made on the contribution of the symphony orchestras culture and the scientific method, which allowed to know how the same was developed , the type of research is documentary, the information collected was based on books, magazines and other publications , it was also field because it was carried out in the place of research, it is worked with a population of 225,741 inhabitants of the canton Riobamba , and the sample was 339 people who were distributed in the different parishes urban and rural , the techniques used were the interviews that were made to connoisseurs and managers of the symphony orchestra of Riobamba as well as to the director of the national symphony, surveys were also carried out aimed at the inhabitants , the instrument that was used was a questionnaire of nine questions , the same ones that helped us with the analyzes in order to reach the conclusions so, the symphonyc music creates spaces for culture strengthening and is accepted in the citizenship , since the symphony orchestra handles a varied repertoire.